Morphological proportions for detection of genetic inheritance in F1 progenies of Arabica (Coffea Arabica L.) - Kumar, Anil; Ganesh, S.; Mishra, M.K.; ., Jayarama (Indian Journal of Agroforestry, 2020)
Plant architecture is composed of several morphological components combined in a certain proportion to produce the phenotype of the particular species. Consequent to the breeding protocols, this proportion changes from one generation to the other and the offspring possess a new proportion dissimilar to their parents. To identify the genetic traits transmitted by the parents, an attempt was made to measure the morphological ratios between the various components of the F1 progenies of dwarf and tall coffee cultivars. The ratios between the changeable characters and with in non-changeable characters were separately calculated in the hybrids and the parents and compared.